Designing the Future: Exploring AI Adoption Effects on Digital Designers in Pakistan - Haroon, Azra; Amna Zulqarnain; Dr. Wajid Zulqarnain (Journal of Peace, Development and Communication, 2024)
Modern technology of Artificial Intelligence (AI) has become a revolution in the present age, and it has been taking a fast momentum over the past few years in Pakistan, many industries of the country are using this advanced technology frequently. We can say without any doubt that the workplace is being changed due to this (AI) technology, though it is vital to investigate how and to what degree it is impacting the digital designers of Pakistan. This study aims to provide insight into AI usage in digital design at the present level, encompassing online and graphic design. Furthermore, to investigate how AI is changing the character of the profession from the viewpoints of industry professionals. It can be analyzed how AI in day-to-day tasks and workflows impacts the industry with a focus on the creative process and the creation of digital products. It can also be viewed whether implementing AI has resulted in the creation of new work processes or if traditional jobs are still being completed with AI tools. Is there a qualitative research methodology used? Have the essential data gathered and examined through reviews of the literature and conversations with pertinent designers who are currently employed in the field? The research findings tell us that the society is divided over the use of AI as there does not exist unanimous understanding on the subject. However, a plethora of software and design processes are making effective use of artificial intelligence, irrespective of the design developer’s preferences for it. Resultantly, the AI appears to have taken over the digital design industry as the designs are being developed in great number with its help. At the same time, the debates and controversies also exist parallel to the growing use of artificial intelligence in design companies.